Game Theory, the Science of Strategy - Matos, M. C.; Ferreira, M. A. M. (EasyChair Preprint Nº 7942, 2025)
This paper makes a simple presentation of strategy games emphasizing their application to management in general. The language used is very straightforward and mathematical symbols are avoided. Mathematical reasoning is presented descriptively. The dominant perspective is critical in that game theory has promised so much but to a certain extent has failed to fulfil its promises, mainly in real world applications. However, recent developments envisage a brighter future for game theory in both from a practical and theoretical aspect.